1998
DOI: 10.1897/1551-5028(1998)017<1835:robaap>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Brain Acetylcholinesterase and Plasma Cholinesterase Activities in Quail (Coturnix Coturnix) After Chlorpyriphos Administration and Effect of Pralidoxime Treatment

Abstract: Abstract-Chlorpyriphos (13 mg/kg) was administered to quail (Coturnix coturnix), and the responses of brain acetylcholinesterase (AChE) and plasma cholinesterase (ChE) were studied. Both enzymes responded rapidly, and the maximal inhibition (76.6 and 86.1%, respectively) ocurred 8 h postadministration. Plasma ChE recovered rapidly, and even on day 4, ChE values of quail that had received chlorpyriphos were higher than those of controls. The recovery of brain AChE activity was slower than that of plasma; it rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
1
5
0
4
Order By: Relevance
“…The CVs for the plasma parameters revealed a ranking of normal homeostatic ranges from narrowest to broadest being P osm ,Hct, plasma ChE activity. Measures and variability of cholinesterase activities in tissues of our quail were consistent with those observed in this species by Soler-Rodriguez et al (1998), who reported mean (CV) brain and plasma ChE activities of 7.32 (11%) mmol substrate hydrolyzed/min/g wet mass and 0.838 (32%) mmol substrate hydrolyzed/min/ml, respectively.…”
Section: Control Brain Che Activity and Pre-exposure Plasma Parameterssupporting
confidence: 89%
“…The CVs for the plasma parameters revealed a ranking of normal homeostatic ranges from narrowest to broadest being P osm ,Hct, plasma ChE activity. Measures and variability of cholinesterase activities in tissues of our quail were consistent with those observed in this species by Soler-Rodriguez et al (1998), who reported mean (CV) brain and plasma ChE activities of 7.32 (11%) mmol substrate hydrolyzed/min/g wet mass and 0.838 (32%) mmol substrate hydrolyzed/min/ml, respectively.…”
Section: Control Brain Che Activity and Pre-exposure Plasma Parameterssupporting
confidence: 89%
“…Permanent inactivation of ChE or aging is dependent on time after exposure. In vitro and in vivo experiments carried out with avian serum and brain ChEs have demonstrated that reactivation using oximes is dependent on the time since exposure [9,10]. Serum BChE activity of G. galloti previously inhibited by paraoxon or dichlorvos did not recover totally in the presence of 2-PAM (see Fig.…”
Section: Discussionmentioning
confidence: 97%
“…ticides, respectively [7,8]. Reactivation of phosphorylated ChE activity using 2-PAM has been applied in laboratory and field studies using birds as bioindicators [5,9,10]. In addition to evaluating ChE activity levels, the ChE reactivation technique is well established as an indicator of exposure to anti-ChE pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent inactivation of ChE or aging is dependent on time after exposure. In vitro and in vivo experiments carried out with avian serum and brain ChEs have demonstrated that reactivation using oximes is dependent on the time since exposure [9,10]. Serum BChE activity of G. galloti previously inhibited by paraoxon or dichlorvos did not recover totally in the presence of 2‐PAM (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical reactivation techniques based on oximes (e.g., pyridine‐2‐aldoxime methochloride [2‐PAM]) and water dilution of samples (i.e., spontaneous reactivation) can be used to discriminate between exposure to OP or CB pesticides, respectively [7,8]. Reactivation of phosphorylated ChE activity using 2‐PAM has been applied in laboratory and field studies using birds as bioindicators [5,9,10]. In addition to evaluating ChE activity levels, the ChE reactivation technique is well established as an indicator of exposure to anti‐ChE pesticides.…”
Section: Introductionmentioning
confidence: 99%